2009
DOI: 10.1007/s10535-009-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerenchyma formation in maize roots

Abstract: Maize (Zea mays L.) is generally considered to be a plant with aerenchyma formation inducible by environmental conditions. In our study, young maize plants, cultivated in various ways in order to minimise the stressing effect of hypoxia, flooding, mechanical impedance or nutrient starvation, were examined for the presence of aerenchyma in their primary roots. The area of aerenchyma in the root cortex was correlated with the root length. Although 12 different maize accessions were used, no plants without aerenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 46 publications
4
42
0
3
Order By: Relevance
“…Both RCS and RCA are accelerated by nutrient deficiencies (Gillespie and Deacon 1988;Drew et al 1989;Elliott et al 1993), reduce radial nutrient transport (Hu et al 2014;Schneider et al 2017a), reduce radial hydraulic conductivity (Fan et al 2007;Schneider et al 2017a), reduce metabolic costs (Zhu et al 2010;Postma and Lynch 2011b;Jaramillo et al 2013;Saengwilai et al 2014;Chimungu et al 2015), are influenced by exposure to ethylene (Lascaris and Deacon 1991b;Lenochová et al 2009;Schneider et al 2017c), and are types of PCD Jiang et al 2010;Schneider et al 2017c). Two ethylene-related genes were upregulated during both RCS and RCA formation (Rajhi et al 2011;Schneider et al 2017c).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both RCS and RCA are accelerated by nutrient deficiencies (Gillespie and Deacon 1988;Drew et al 1989;Elliott et al 1993), reduce radial nutrient transport (Hu et al 2014;Schneider et al 2017a), reduce radial hydraulic conductivity (Fan et al 2007;Schneider et al 2017a), reduce metabolic costs (Zhu et al 2010;Postma and Lynch 2011b;Jaramillo et al 2013;Saengwilai et al 2014;Chimungu et al 2015), are influenced by exposure to ethylene (Lascaris and Deacon 1991b;Lenochová et al 2009;Schneider et al 2017c), and are types of PCD Jiang et al 2010;Schneider et al 2017c). Two ethylene-related genes were upregulated during both RCS and RCA formation (Rajhi et al 2011;Schneider et al 2017c).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
“…Presumably, RCS which culminates in a non-continuous epidermis, has no utility in hypoxic conditions. In addition, the formation of RCA begins in middle cortical cell files and progresses in a radial pattern leaving spokes of cortical tissue connecting outer cortical cell files with inner cortical cell files (Arikado 1955;Thomson et al 1990;Kawai et al 1998;Lenochová et al 2009), in contrast to RCS which begins in outer cortical cell files and progresses inward towards the endodermis until the entire cortex has senesced (Holden 1975;Henry and Deacon 1981). The development of RCS is constitutive and is developed primarily in small temperate grains in the Poaceae family (Deacon and Mitchell 1985;Yeates and Parker 1985;Jupp and Newman 1987;Liljeroth 1995).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
“…Thus, it has been hypothesized that RCA formation has utility under a variety of edaphic stresses by reducing the metabolic costs of soil exploration (Lynch andBrown, 1998, 2008). RCA, formed in maize (Zea mays) by programmed cell death (Lenochová et al, 2009), reduces root nutrient content and respiration (Fan et al, 2003). Zhu et al (2010) found that maize genotypes with high RCA formation under drought had 5 times greater biomass production and 8 times greater yield than closely related genotypes with less RCA.…”
mentioning
confidence: 99%
“…Since ethylene is involved in signaling RCA formation (Drew et al, 2000), a possible increase in ethylene production due to potassium deficiency (Jung et al, 2009) may also result in increased RCA formation. Since RCA can form constitutively in maize plants under optimal conditions (Fan et al, 2003;Lenochová et al, 2009;Burton, 2010;Zhu et al, 2010), it may have value for potassium acquisition even if it is not induced by low potassium availability.…”
mentioning
confidence: 99%
See 1 more Smart Citation